Hubungan Usia, Paritas DAppN Jarak Kehamilan dengan Kejadian Anemia pada Ibu Hamil Multipara di Praktek Mandiri Bidan Kelurahan Sukajadi Kabupaten Banyuasin 2020 - Lia Novianti; Helni Anggraini; Sendy Pratiwi Rahmadhani (Universitas Batanghari Jambi, 2022)
Anemia in pregnant women is one of the most common health problems experienced by pregnant women. Causes of anemia in pregnant women include maternal compliance in consuming FE tablets, parity, age of pregnant women, number of Antenatal Care (ANC) visits and gestational spacing. This study aims to determine the relationship between age, parity and pregnancy distance with the incidence of anemia in pregnant women. The study used an analytical survey with a cross sectional approach. The population of all multiparous pregnant women was 186 respondents. The sampling technique used systematic random sampling with a sample of 65 respondents. Collecting data on the variables of anemia, age, parity and pregnancy interval using a checklist. The research was conducted at the Independent Midwife Practice of Sukajadi Village, Banyuasin Regency in July-August 2021. Data were analyzed using the Chi-Square test. More than half of pregnant women with anemia (66.2%), more than half of pregnant women with high risk age (55.4%), more than half of pregnant women with low priority (52.3%), and most pregnant women with low-risk pregnancies (75.4%). There is no relationship between age and the incidence of anemia, p value 0.052 and odds ratio 3.267, there is a parity relationship with the incidence of anemia, p value is 0.004 and odds ratio is 5.200, there is a relationship between pregnancy distance and the incidence of anemia, p value is 0.007 and odd ratio is 11.250. In this study is that the age of pregnant women has no relationship with the incidence of anemia, parity and distance between pregnancies has a relationship with the incidence of anemia in multiparous pregnant women.